Detection of The TNFSF Members BAFF, APRIL, TWEAK and Their Receptors in Normal Kidney and Renal Cell Carcinomas - Vassiliki Pelekanou; George Notas; Katerina Theodoropoulou; Marilena Kampa; Dimitrios Takos; Vassilia-Ismini Alexaki; Jelena Radojicic; Frank Sofras; Andreas Tsapis; Efstathios N. Stathopoulos; Elias Castanas (Analytical Cellular Pathology)
In advanced renal cell carcinoma (RCC), surgery combined with systemic chemotherapy and immunotherapy have had limited effectiveness. Therapeutic modalities targeting VEGF, PDGF, and c-kit using tyrosine kinase inhibitors and m-TOR using specific biologic factors are in development. Therapeutic approaches targeting TNF-alpha have shown limited efficacy, while anti-TRAIL (TNFSF10) antibodies have shown enhanced activity. The presence and potential significance of other members of the TNFSF has not been investigated. Here, we assayed the TNFSF members APRIL, BAFF, TWEAK and their receptors (BCMA, TACI, BAFFR, Fn14) in 86 conventional type clear cell RCC, using immunohistochemistry and correlated our findings with histological data and, in a limited series, follow-up of patients. We observed a differential expression of these TNFSF ligands and receptors in cancerous and non-cancerous structures. BAFF was found in all RCC; APRIL expression is associated with an aggressive phenotype, correlating negatively with patients' disease-free survival, while TWEAK and its receptor Fn14 are heterogeneously expressed, correlating negatively with the grade and survival of RCC patients. This is the first study, presenting together the TNFSF members APRIL, BAFF, TWEAK and their receptors in different areas of normal renal tissue and RCC, suggesting a potential role of these TNFSF members in renal tumor biology.